Tricuspid stenosis: An emerging disease in cardiac implantable electronic devices era. Case report and literature review. Issue 6 (June 2017) - Husain, Aysha; Raja, Faris Tufail; Fatallah, Ahmed; Fadel, Bahaa; Alsanei, Aly; Raja, Fahad Tufail; AlGhamdi, Bandar
Abstract: Tricuspid valve dysfunction and in particular tricuspid stenosis has recently been described secondary to cardiac implantable electronic devices. The valve is subjected to different mechanisms of injury related to the endocardial lead passing through its plane. The lead can form a loop or perforate one of the leaflets and initiate inflammatory response and fibrotic changes. Multimodality cardiac imaging is required to diagnose this clinical entity and decide on the best treatment plan. Here we present a case of a young female who developed tricuspid stenosis secondary to permanent pacemaker lead that was implanted 24 years before. We performed a review for all cases reported in the literature with a similar condition and various treatment approaches. <Learning objectives: 1. Tricuspid valve dysfunction can develop secondary to cardiac implantable electronic devices. Tricuspid regurgitation is the most common valve lesion however, tricuspid stenosis is reported as well. 2. Endocardial leads can cause injury to the valve initiating a cascade of inflammatory response and fibrosis. 3. Trans-thoracic echocardiography is the initial diagnostic modality but visualization of lead injury requires further cardiac imaging such as cardiac computed tomography and trans-esophageal echocardiography. 4. Various treatment modalities are reported in the literature; medical therapy, percutaneous valvoplasty; and surgery.>